A comparative study of polydopamine vs. glass ionomer cement for adhesion mechanisms on enamel and dentin using SEM and shear bond strength evaluation - Lakshmi Nidhi Rao; Soumyajit Sarkar; Aditya Shetty; Heeresh Shetty; Shraddha Shetty; Roshan Noor Mohamed; Sakeenabi Basha; Ajinkya Pawar; Mohmed Isaqali Karobari (Scientific Reports)
Abstract Polydopamine (PD), inspired by the wet adhesion mechanism of mussel foot proteins, has emerged as a promising adhesive material with wide-ranging applications. This study aimed to compare the adhesive properties of PD and Glass Ionomer Cement (GIC) on enamel and dentin substrates, evaluating PD’s potential as an alternative adhesive in dental practice. A total of 120 human premolars were prepared, with 80 teeth allocated for Scanning Electron Microscopy (SEM) analysis and 40 teeth reserved for shear bond strength testing. The 80 teeth for SEM were divided into four groups (n = 20 per group) based on the adhesive used (PD or GIC) and the substrate (enamel or dentin). The bond interfaces were analysed under SEM following adhesive self-polymerization. Statistical analysis using the Mann-Whitney U test (p < 0.05) revealed that GIC and PD showed more microcracks when bonded to dentin compared to enamel, with the PD-enamel group showing the fewest microcracks. For shear bond strength testing, the 40 remaining teeth were divided into four groups (n = 10 per group) according to the same adhesive-substrate combinations. The results analysed using the Kruskal-Wallis test (p < 0.001), indicated that PD bonded to enamel exhibited the highest bond strength, followed by PD-dentin, GIC-enamel, and GIC-dentin. These findings were consistent with the SEM analysis, demonstrating that PD provides superior bonding to enamel and outperforms GIC in both bond strength and interface quality. This study suggests that PD is a viable alternative to GIC, particularly for enamel bonding, and further research is recommended to assess its long-term clinical performance.